Penerapan Pendekatan Pembelajaran Berdiferensiasi dalam Pengelolaan Kelas (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to comprehensively describe the implementation of differentiated learning in classroom management and analyze its impact on students’ learning outcomes, particularly in mathematics subjects. The research method employed is a literature review by examining various scholarly sources such as national and international journals, educational textbooks, and relevant research articles. The findings indicate that differentiated learning is a pedagogical approach that places students at the center of the learning process by accommodating individual differences in terms of readiness, interests, and learning styles. This approach has proven effective in enhancing students’ motivation, active engagement, and conceptual understanding of mathematical content. Although its implementation presents several challenges, including classroom management complexity, time constraints, and limited learning resources, numerous studies report significant improvements in post-test scores, learning activities, and overall learning achievement following the application of differentiated learning strategies. Therefore, differentiated learning can serve as a strategic solution to create an inclusive, adaptive, and learner-centered educational environment, ultimately improving the quality of teaching and learning, especially in mathematics education.